Pengoplos BBM Eceran Tinjauan Fiqih Jinayah dan Implikasinya di Nagari Cubadak Menatawai - Muhammad Qadafi Arifin; Hendri Hendri (AHKAM, 2026)
The widespread practice of fraud by retail fuel oil (BBM) traders in Pariaman City, particularly in the form of fuel adulteration, indicates that government supervision of retail BBM sales activities remains weak, even though such activities legally require official permits. This study aims to identify the forms of violations in the practice of BBM adulteration carried out by retail traders in Pariaman and to analyze them from the perspective of fiqih jinayah. This study employed a field research method with a qualitative approach. The research was conducted at Pengadilan Negeri Pariaman, with data collected through interviews, observation, and documentation, and then analyzed using the descriptive-analytical method. The results showed that the practice of BBM adulteration was carried out in several forms, namely mixing fuel with coloring agents obtained through online platforms and blending them into genuine Pertamax, as well as mixing Pertamax with kerosene to produce adulterated fuel in order to obtain an additional profit of around Rp2,000 per liter. From the perspective of fiqih jinayah, this practice falls into the category of jarimah ta’zir, namely a criminal act for which the determination of sanctions is left to the government. In addition, the act is also classified as a form of fraud prohibited in Islamic teachings. This study concludes that the practice of adulterating retail BBM constitutes a violation of both positive law and Islamic criminal law, so the perpetrators may be subject to criminal sanctions of imprisonment and fines as reflected in Putusan Pengadilan Negeri Pariaman Nomor 179/Pid.Sus/2023/PN. These findings contribute to strengthening the study of Islamic criminal law, particularly fiqih jinayah, while also providing practical implications for strengthening government supervision of the distribution of retail BBM.